Feature extraction and image processing - Nixon, Mark S.; Aguado, Alberto S. (Academic Press/Elsevier Ltd., 2008)
'Feature Extraction and Image Processing' takes one of the prime targets of applied computer vision, feature extraction and uses it to provide an essential guide to the implementation of image processing and computer vision techniques.